Racial/Ethnic Disparities in Inflammatory Gene SNPs as Predictors of High Risk for Symptom Burden in Patients with Multiple Myeloma 1 Year Post-Diagnosis - Shi, Qiuling (Cancer, 2014)
BACKGROUND: We conducted a study to determine whether any regulatory single-nucleotide polymorphism (SNP) in an inflammatory gene was associated with high symptom burden in patients 1 year after diagnosis with multiple myeloma (MM). METHODS: MM patients rated symptoms using the MD Anderson Symptom Inventory (MDASI)-MM module and provided buccal-swab DNA samples. SNPs for 4 cytokine genes (IL6 –174G>C, IL1β –511C>T, TNFα –308G>A, IL10 –1082G>A) were tested. Logistic regression models were used to identify SNPs that might predict moderate/severe symptoms (rated ≥4 on the MDASI-MM’s 0–10 scale). To evaluate the relationship between SNPs and overall symptom burden, we used 2-step cluster analysis to divide patients into subgroups with high or low symptom levels. RESULTS: Of the 344 patients enrolled, 41% had high overall symptom burden. The most prevalent moderate/severe symptoms were fatigue (47%), pain (42%), numbness (38%), and bone aches (32%). For non-Hispanic whites, the IL1β –511 CC genotype was associated with high overall symptom burden (OR, 2.35; 95% CI, 1.25–4.72; P = .004), while IL6 –174 GG genotype predicted less moderate/severe fatigue (OR, 0.53; 95% CI, 0.29–0.88; P = .013). For other patients, IL6 –174 GG genotype predicted moderate/severe pain (OR, 3.36; 95% CI 1.23–13.64; P = .010). CONCLUSIONS: Our results support growing evidence that inflammation is associated with cancer-related symptoms and suggest that racial/ethnic factors contribute to this association.